X²-2x-35 | x-7
x²-7x x+5
5x-35
5x-35
0
(x-7)(x+5)=x²-7x+5x-35=
x²-2x-35
-4x²-x+5 | 4x+5
-4x²-5x -x+1
4x+5
4x+5
0
(4x+5)(-x+1)=-4x²-5x+4x+5=
-4x²-x+5
6x²+7x-3 | 2x+3
6x²+9x 3x-1
-2x-3
-2x-3
0
(2x+3)(3x-1)=6x²+9x-2x-3=6x²+7x-3
6x³+7x²-6x+1 | 3x-1
6x³-2x² 2x²+3x-1
9x²-6x
9x²-3x
-3x+1
-3x+1
0
(3x-1)( 2x²+3x-1)=6x³-2x²+9x²-3x-3x+1=6x³+7x²-6x+1
6x³+11x² -1 | 2x²+3x-1
6x³+9x²-3x 3x+1
2x²+3x-1
2x²+3x-1
0
( 2x²+3x-1)(3x-1) =6x³-2x²+9x²-3x-3x+1=6x³+7x²-6x+1
15x³- x²+ 8x-4 | 3x²+x+2
15x³+5x²+10x 5x-2
-6x²-2x-4
-6x²-2x-4
0
(3x²+x+2)(5x-2)=15x³-6x²+5x²-2x+10x-4=15x³-x²+8x-4